The Construction of Resistance in Ibrahim Touqan's “Mawtini” Song Lyrics: New Historicism Analysis - Lestari, Septi; Yurisa, Penny Respati (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
The hegemonic attempts made by the British and European Jews triggered resistance from the Palestinian people. The resistance is manifested in physical and non-physical struggles, including literary works. This research aims to reveal the construction of resistance in Ibrahim Touqan's Mawtini by using the theory of New Historicism by Stephen Greenblatt. Literary readings are juxtaposed with non-literary texts in order to find the historical background of colonialism in Palestine in the British Mandate era and the diaspora of Jews from Europe. This research is a descriptive qualitative type. The data of this research is in the form of mawtini song lyrics which are then read together with two non-literary books to understand the historical substance behind the song lyrics. Based on the results of the research, it was found that the construction of resistance in this song is structured through the perspective of the people seeing their homeland, the hope for a resolution to the conflict, the importance of the role of youth to fight, the purpose of the resistance and the methods taken in resistance to hegemony efforts over the land of Palestine. Abstrak Upaya hegemoni yang dilakukan oleh Inggris dan Yahudi Eropa memicu perlawanan dari rakyat Palestina. Perlawanan tersebut diwujudkan dalam perjuangan fisik dan non-fisik, termasuk di dalamnya adalah karya sastra. Penelitian ini bertujuan untuk mengungkapkan konstruksi perlawanan di dalam lirk lagu Mawtini karya Ibrahim Touqan dengan menggunakan teori New Historicism oleh Stephen Greenblatt. Pembacaan sastra disandingkan dengan teks non sastra agar menemukan latar belakang sejarah kolonialisme di Palestina di era Mandat Inggris serta diaspora kaum Yahudi dari Eropa. Penelitian ini berjenis kualitatif deskriptif. Data penelitian ini berupa lirik lagu mawtini yang kemudian dibaca bersamaan dengan dua buku non-sastra untuk memahami substansi sejarah di balik lirik lagu tersebut. Data dikumpulkan menggunakan teknik baca-catat. Sedangkan teknik analis data melalui tahap reduksi data, penyajian, dan penarikan kesimpulan. Berdasarkan hasil penelitian, ditemukan konstruksi perlawanan di dalam lagu ini disusun melalui perspektif rakyat melihat tanah airnya, harapan adanya resolusi atas konflik, pentingnya peran pemuda untuk melakukan perlawan, tujuan dari perlawanan tersebut serta cara-cara yang ditempuh dalam melakukan perlawanan terhadap upaya hegemoni di atas negeri Palestina.